Real-world effectiveness and safety of glecaprevir/pibrentasvir therapy in patients with chronic hepatitis C virus infection in Switzerland (Swiss Medical Weekly, 2021)
AIM OF THE STUDY In the era of pangenotypic treatment regimens against hepatitis C virus (HCV) infection, data from postmarketing observational studies are crucial to better understand the treatment patterns used in specific countries and treatment outcomes under real-life conditions. We report data from Switzerland from an ongoing, multinational postmarketing observational study on the pangenotypic treatment regimen of glecaprevir (GLE; NS3/4A protease inhibitor) and pibrentasvir (PIB; NS5A inhibitor), coformulated as GLE/PIB. METHODS Adults infected with chronic HCV genotypes 1–6 were eligible to participate in the postmarketing observational study if they started GLE/PIB at the treating physician’s discretion. The primary objective was to evaluate the effectiveness of GLE/PIB based on sustained virological response 12 weeks after completion of treatment (SVR12); secondary outcomes included patient-reported outcomes (Fatigue Severity Scale, Work Productivity and Activity Impairment Questionnaire, Pictorial Representation of Illness and Self Measure tool) and safety data. RESULTS In Switzerland, 109 patients were enrolled, and 107 patients received ≥1 dose GLE/PIB (94.4% non-cirrhotic; 43.9%/14.0%/29.0%/13.1% GT1/GT2/GT3/GT4; 89.7% treatment-naïve; 91.6% assigned to an 8-week GLE/PIB regimen). Overall, 95 of 98 patients with sufficient follow-up data (96.9%) achieved SVR12 (95% confidence interval [CI] 91.4% to 99.0%), and 91.6% in the safety population (including six non-virological failures). The three treatment failures were due to relapse. All three failures were GT3, without cirrhosis and treatment naïve. Patient-reported outcomes improved as well. GLE/PIB was well tolerated with no serious adverse events and no adverse events leading to discontinuation or interruption of GLE/PIB treatment. CONCLUSION These real-world effectiveness and safety data of GLE/PIB in patients from Switzerland were consistent with those seen in the multinational registration trials. (Trial registration number: Clinicaltrials.gov: NCT03303599.)